Factors antecedents of student learning satisfaction: evidence of online learning in Indonesia - Puja, Ida Bagus Putu; Agung, Anak Agung Gede; Sunu, I Gusti Ketut Arya; Ariawan, I Putu Wisna (International Journal of Evaluation and Research in Education (IJERE), 2024)
COVID-19 has had a broad impact on learning in schools. There is a change in the learning model in online mode, this change also affects changes in student learning behavior including how to increase student learning satisfaction through online learning. Many studies have discussed online learning, but it is still limited to how student learning satisfaction is formed during online learning. This study examines the effect of perceived service quality, social media utilization, teacher techno-pedagogical competencies, and students’ motivation to learn online on student learning satisfaction. A total of 345 state vocational school students in Gianyar Regency, Bali, Indonesia were involved in this study. Structural Equation Modeling (SEM) analysis was used to test the hypothesis of this study. The results of the study show that students’ online learning satisfaction is significantly influenced by the quality of educational services and students’ online learning motivation. Meanwhile, other antecedent factors such as the use of social media and teacher competence proved to not affect student learning satisfaction. This study also found that students’ learning motivation was influenced by the quality of educational services. Meanwhile, the factors of using social media and teacher competency did not significantly influence student learning motivation. Lastly, this study also revealed that students’ online learning motivation proved to have no role as a mediator on the effects of quality of education services, use of social media, and teacher competency on the learning satisfaction of vocational school students.